Smart Board Media for Reading Instruction in Elementary Schools - Asmaria Asmaria; Masitoh Masitoh; Meutia Rachmatia (Universitas Pendidikan Ganesha, 2026)
Reading instruction in elementary schools often faces challenges such as low student interest and engagement due to conventional methods that are less interactive, highlighting the need for more engaging and innovative learning media. This study aims to analyze the implementation of Smart Board media in reading instruction and its impact on students’ motivation, engagement, and reading comprehension. The method used is a Systematic Literature Review (SLR) guided by PRISMA, through a search of scholarly articles on Google Scholar using four main keywords: Smart Board, learning media, reading instruction, and elementary school, which were then screened to obtain 10 most relevant articles for analysis. The analysis results indicate that the implementation of Smart Board can significantly enhance student engagement, learning motivation, and reading comprehension, as the media presents material interactively, visually, and audibly, encouraging active student participation in the learning process. In conclusion, Smart Board is effective for reading instruction in elementary schools and has positive implications, including improving literacy quality, developing digital learning strategies, and emphasizing the need for teacher training to maximize the use of interactive media. The findings of this study suggest that Smart Boards can serve as an innovative alternative to digital learning tools and help improve students’ literacy skills.